Hemoglobinopathy and pediatrics in the time of covid-19 (2020)
Introduction: It is important to know if patients with hemoglobinopathy could be more susceptible to COVID-19. Objective: Analyze SARS-CoV-2 infection in pediatric patients with hemoglobinopathy. Methods: Using the online platforms LILACS, PUBMED and EMBASE, on 17- JUL-2020 a search was made for the terms COVID-19 and SARS-CoV-2 associated with “sickle cell”, “thalassemia” and “hemoglobinopathy”. Results: There were 623 pediatric and adult patients with sickle cell disease (SCD) or beta thalassemia (BT) and COVID-19. Total mortality rate was 6.42%. No pediatric patient with BT has been described. So, our analysis focused on children and adolescents with SCD: there were 121 pediatric patients, one adolescent died, prophylactic anticoagulation was prescribed to six patients, 11.76% needed intensive care unit, blood transfusion was prescribed in 29.70%. Vaso-occlusive crisis (VOC) and acute chest syndrome (ACS) were the main clinical manifestations in SCD. Discussion: Pediatric patients with SCD and COVID-19 have a low mortality rate when compared to adults, although is higher than the global pediatric population with COVID-19 (0−0.67%). The comorbidities associated with age and the long-term complications inherent to hemoglobinopathies may contribute to the increased mortality outside the pediatric age group. In SCD the clinical manifestations, both in children and adults, are VOC and ACS, and there was increase in blood requirement. Pediatric SCD patients with COVID-19 need more intensive care unit than the global pediatric population (3.30%). Conclusion: Despite pediatric population with SCD needs more intensive care, the outcome after infection by COVID-19 is favorable